2010
DOI: 10.1111/j.1365-2591.2009.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of root filled molar teeth restored with glass fibre bundles

Abstract: The insertion of glass fibres into MOD cavity preparations and restoring them with composite resin was not different than molar teeth filled with composite resin only in terms of fracture resistance. Fibres placed into MOD cavities do not reinforce teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
3
18
0
2
Order By: Relevance
“…It is well established that endodontic treatment in MOD prepared maxillary premolars has a remarkable negative effect on the fracture resistance 3,4,5,6,9. This fact was confirmed by the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is well established that endodontic treatment in MOD prepared maxillary premolars has a remarkable negative effect on the fracture resistance 3,4,5,6,9. This fact was confirmed by the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The loss of marginal ridges, the removal of pulp chamber roof along with inner dentin (axial walls) and the resultant cuspal deflection,1,3,4,5,6 along with the loss of the protective feedback mechanism in the non-vital teeth contribute to the high fracture susceptibility of the teeth 7. In particular, a high incidence of fracture in ET maxillary premolars has been reported due to the susceptibility of their anatomic form to separation, unfavorable crown/root proportion and their exposure to both shear and compressive forces 8,9…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that the polyethylene fibers had a stress-modifying effect along the restoration-dentin interface, and the bonding ability of fibers in combination with the resin might have increased the fracture strength of the tooth by keeping both cusps together. However, Rodrigues et al [21] concluded in a recent paper that fibers placed into MOD cavities did not reinforce teeth, but they may have a protective effect on fracture propagation towards the pulp chamber floor. These inconsistencies could be related to the different angle whereby the specimens were loaded.…”
Section: Discussionmentioning
confidence: 99%
“…The woven network allows fiber wetting and the infusion of the bonding resin; this enhances the transfer of forces acting on the PWT. Previous studies showed that this network changed the stress dynamics at the enamelcomposite material interface [19], but the effect on fracture resistance of endodontically treated teeth remains controversial [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…5 The fracture potential of root canal filled teeth has been studied extensively, however, no definite causal relation ship between fracture and the type of restoration has been established, and controversies remain about which materials or techniques are best for their restoration. 6 In many situations, the remaining coronal tooth structure of endodontically treated teeth is insufficient to anchor coro nal restorations. 5 Therefore, endodontically treated teeth often require post-and-core restorations for retention purposes because of extensive structural defects resulting from caries and access cavity preparation.…”
Section: Introductionmentioning
confidence: 99%